1994
DOI: 10.12968/bjon.1994.3.16.816
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance charts: do they measure up?

Abstract: Many current nursing activities are performed without regular reviews of their usefulness. The recording of fluid gains and losses on a fluid balance chart is one such activity. This article explores the practice of fluid monitoring on the wards of a university teaching hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 2 publications
3
28
0
1
Order By: Relevance
“…However, there was a trend towards smaller samples being less accurately assigned than larger samples (Table 4). This supports the previous studies demonstrating that nurses tend to overestimate fecal weight (Daffurn et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, there was a trend towards smaller samples being less accurately assigned than larger samples (Table 4). This supports the previous studies demonstrating that nurses tend to overestimate fecal weight (Daffurn et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Given that both of these are impractical in the clinical setting, nurses routinely characterize fecal output visually. However, nurse characterization of fecal consistency has been shown to be only fairly reliable (Allen et al, 1994), while nurse characterization of fecal weight may overestimate the actual amount (Daffurn et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Error between measurements varied up to 36% among individual patients (Wise et al, 2000). In a subsample of nurses (n = 45), Daffurn et al (1994) found that intake and output measurement of simulated fluid samples were slightly overestimated, with significant overestimations noted for output volumes involving wet beds or IV fluid leaks (p < 0.05). In a subsample of nurses (n = 45), Daffurn et al (1994) found that intake and output measurement of simulated fluid samples were slightly overestimated, with significant overestimations noted for output volumes involving wet beds or IV fluid leaks (p < 0.05).…”
Section: Literature Reviewmentioning
confidence: 92%
“…The studies involved qualitative (Kalisch, 2006), quantitative (Mank, Semin-Goossens, Lelie, Bakker, & Vos, 2003;Wise, Mersch, Racioppi, Crosier, & Thompson, 2000), or mixed methods (Daffurn et al, 1994), with only one study involving patients with cancer as the primary sample (Mank et al, 2003). Structured interviews and observations of nursing practices (n = 105) for intake and output measurements and weights (Kalisch, 2006) or surveys (n = 143) on nursing perceptions of fluid balance records (Daffurn et al, 1994) produced similarities in identified barriers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation